Victor Brauner. Atrapulsion, peinture à la caséine sur toile présentant un important réseau de craquelures en cuvette - Cristina Cojocaru Pingeot (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Atrapulsion is a 1938 casein paint on canvas by Victor Brauner. The painting has a severe end extensive network of opened drying cracks with lifted paint and many losses on edges. The artist used for this painting inappropriate materials. Loose paint was fixed with Paraloid B72® which left shiny residues on the surface. The research for an accurate diagnosis required tests that led to the reproduction of the drying cracks observed on the original work. The experimental study compares solvents (including silicone solvents) for the removal of adhesive residues from a porous surface. The conservation treatments lead to a diminution of the canvas and ground distortions, and to the removal of resin residues.